The effect of scutellaria baicalensis and its active ingredients on major depressive disorder: a systematic review and meta-analysis of literature in pre-clinical research - Ma, Ying; Zhou, Xun; Zhang, Feng; Huang, Cuiyun; Yang, Hong; Chen, Wansheng; Tao, Xia (Frontiers in Pharmacology, 2024)
Background: Scutellaria baicalensis, the dry root of scutellaria baicalensis georgi, is a traditional Chinese medicine with long. In clinic, scutellaria baicalensis is commonly used in prescription for the treatment of depression. Additionally, numerous pre-clinical studies have shown that Scutellaria baicalensis and its active constituents are effective for depression. In this study, we aims to systematically review the roles of scutellaria baicalensis in depression and summarize the possible mechanism.Methods: A systematic review and meta-analysis were conducted to analyze the existing studies on the effects of scutellaria baicalensis on depression in animal models. Briefly, we searched electronic databases including Pubmed and Embase for preclinical trial studies from inception to September 2023. The items in each study were evaluated by two independent reviewers, and meta-analyses were performed on scutellaria baicalensis-induced behavioral changes in the study. Finally, random effects model is used to collect data.Results: A total of 49 studies were identified, and 13 studies were included in the final analysis. They all reported the different antidepressant effects of scutellaria baicalensis and the underlying biological mechanisms. Among the included 13 studies, the results of eight articles SPT[SMD=-2.80, 95%CI(-4.03,-1.57), P<0.01], the results of the nine articles OFT[SMD=-2.38, 95%CI(-3.53,-1.23), P<0.01], and the results of two articles NSFT[SMD=-2.98, 95%CI(-3.94,-2.02), P<0.01] were significantly different from the control group. The risk of bias was moderate in all studies, however, there was a significant heterogeneity among studies.These results preliminarily suggest that scutellaria baicalensis can alleviate depressive behaviors and modulate underlying mechanisms, which is expected to be a promising antidepressant.